Obesity and central obesity in Indonesia: evidence from a national health survey (Medical Journal of Indonesia, 2018)
Background: Obesity and central obesity have become serious public health problems in developing countries such as Indonesia. Although 10 years have passed since the largest national health survey was conducted in 2007, no further analysis and publication concerning obesity and central obesity in Indonesia have been conducted based on the survey. The aim of this study is to determine the prevalence of obesity and central obesity, and its association with sociodemographic characteristics and comorbidities in Indonesia.Methods: A cross-sectional study was conducted based on the National Basic Health Survey 2007 using total sampling method from 33 provinces. Obesity is defined as body mass index ≥25 according to the Asia-Pacific standard for obesity. Central obesity is defined as waist circumference >90 cm for men and > 80 cm for women according to the Asia-Pacific standard for central obesity. Results: The prevalence of obesity and central obesity in the Indonesian adult population are 23.1% and 28%, respectively. Both rates are higher in females than in males. Obesity and central obesity are associated with the risk of diabetes and hypertension.Conclusion: Prevalence of obesity and central obesity is high in the Indonesian adult population. Interventional programs are important to promote awareness of obesity and healthy lifestyle changes in the community.